A A STUDY OF MUSCULOSKELETAL DISORDERS AMONG ADULT POPULATION IN RURAL FIELD PRACTICE AREA OF A MEDICAL COLLEGE IN WESTERN MAHARASHTRA - SHRAVAN TALKAD,; PUJA DUDEJA,; AVIN B R ALVA, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study was conducted to find the prevalence of selected musculoskeletal disorders (MSDs) in the rural field and to describe these disorders concerning certain sociodemographic factors. Methods: The study is a community-based cross-sectional study undertaken in the village of western Maharashtra. A total of 330 subjects were included by systematic random sampling. The study included all adults (>18 years) and permanent residents of the study area. The interview of subjects was conducted through contacting by door-to-door survey in the community. A predefined questionnaire was used to interview the included subjects. Results: The prevalence of MSDs was 33.03%. The development of MSD was more common in patients with >60 years (56.2%). Moreover, illiterate (52.8%), professionally working (41.1%), overweight (51.8%), married group (36.9%), and heavy workers (54.9%) showed significant differences in the incidence of MSDs. Conclusion: The MSDs in the present study had a higher prevalence with certain sociodemographic factors determining its occurrence. The mainstay for the prevention of MSDs is early diagnosis, education of the people in rural areas about the importance of early diagnosis, and motivating them to seek early treatment.